2016
DOI: 10.1166/jbn.2016.2215
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Core Nanocapsules Act as a Drug Shuttle Through the Blood Brain Barrier and Reduce Glioblastoma After Intravenous or Oral Administration

Abstract: Lipid-core nanocapsules (LNC) are formed by an organogel surrounded by poly(epsilon-caprolactone) and stabilized by polysorbate 80. LNCs increase the concentration of drugs in the brain after oral or intravenous administration. We proposed to determine whether the drug is released from the LNC to cross the blood brain barrier (BBB) or the drug-loaded LNCs can cross the BBB to release the drug. We synthesized a Rhodamine B-polymer conjugate to prepare a fluorescent-labeled LNC formulation, and intravital micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 41 publications
2
31
0
2
Order By: Relevance
“…29,36 Moreover, in this study, we confirmed that LNC easily penetrates cell cytoplasm, indicating that intracellular pathways are the target of LNC or delivered drugs. Indeed, data presented in this study clearly show that LNC or AcE-LNC treatments improve the apoptosis of melanoma cells in different conditions associated with tumor microenvironment.…”
Section: Discussionsupporting
confidence: 70%
“…29,36 Moreover, in this study, we confirmed that LNC easily penetrates cell cytoplasm, indicating that intracellular pathways are the target of LNC or delivered drugs. Indeed, data presented in this study clearly show that LNC or AcE-LNC treatments improve the apoptosis of melanoma cells in different conditions associated with tumor microenvironment.…”
Section: Discussionsupporting
confidence: 70%
“…The enhancing effect was possibly due to quercetin protection against extensive gastric and intestinal degradation [62]. Besides, PCL nanocapsules were shown to be absorbed intact by mouse intestinal epithelia [63] and also taken up by M cells [64]. Whether or not absorbed quercetin-loaded particles reach the circulation [65] and Leishmania-infected skin macrophages remained to be determined.…”
Section: Oral Treatmentmentioning
confidence: 99%
“…For example, rhodamine 6-labeled LNC drug shuttles were designed to deliver drugs across the BBB and into brain tissue with high efficiency, thus reducing glioblastoma after oral or intravenous administration. [22] Additionally, several notable examples of “nanomedicines” have been translated from bench to bedside, including liposomal Doxorubicin and Doxil. [93] Nanomedicine-based drugs in clinical trials or that have been clinically approved for the treatment of diseases related to the nervous system are shown in (Table 3).…”
Section: Diagnostic and Therapeutic Applications Of Nanotechnology Inmentioning
confidence: 99%